THE IMPACT OF CARRYING BACKPACK AND TREKKING POLES ON ENERGY EXPENDITURE DURING UPHILL HIKING IN THE RAMKHAMHAENG NATIONAL PARK, SUKHOTHAI PROVINCE - UDOMTAKU, Kacha; CHAIMING, Panida (Journal of Sports Science and Technology, 2024)
A carrying backpack is an essential tool while trekking whereas a trekking pole helps support the balance of the body while walking up the hill, reduce fatigue, and enhance physical balance. Since there was no conclusion about the impacts on energy expenditure during trekking in Ramkhamhaeng National Park, Sukhothai; this study aims to compare the impact of carrying backpack and trekking pole on energy expenditure, heart rate, and walking time for trekking in Ramkhamhaeng National Park, forty-eight tourists (aged 20 – 40 years old) selected by using purposive sampling technique. These group of participants were divided into 4 groups of 12 : 1) a group without carrying backpack and without trekking pole, 2) a group using only trekking poles, 3) a group using only carrying backpack, and 4) a group using both carrying and trekking pole.The load of the carrying backpack was not heavier than 30 percent of body weight. Subjects wear Garmin Forerunner 245 activity watches during trekking up Khao Luang Peak. The energy expenditure, heart rate, and walking time were then compared. The results showed that the energy expenditure and heart rate in the group using both carrying backpacks and trekking poles were higher and different from the group without carrying backpack with statistical significance (p<0.05). On contrary, the group using trekking poles, both with and without carrying backpacks spent less time for walking than the group without trekking poles. Our results indicate that using trekking poles, with or without carrying backpacks, had an impact on increasing energy expenditure, heart rate, and walking speed. (Journal of Sports Science and Technology 2024; 24(1): 30-39)) (Received: 11 September 2023, Revised: 18 December 2023, Accepted: 25 December 2023) *Corresponding author: Kacha UDOMTAKU Faculty of Sports and Health Science, Thailand National Sports University Sukhothai Campus, Sukhothai, 64000, THAILAND E-mail: kacha_u@hotmail.com